Mole's in love - Bedford, David, 1969-; Beardshaw, Rosalind (London : Egmont, 2009)
Despite Morris' poor eyesight, he wanders off to the barnyard in search of love, but he finds it difficult to find someone that fits all his criteria.
2.3
K-3
Keywords: Moles (Animals) -- Juvenile fiction; Vision -- Juvenile fiction; Love -- Fiction; Moles (Animals) -- Fiction; Vision -- Fiction; Love -- Fiction; Moles (Animals) -- Fiction; Vision -- Fiction